2007
DOI: 10.1038/modpathol.3800957
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling pathway analysis in renal cell carcinoma in young patients

Abstract: Renal cell carcinomas in young patients constitute a morphologically and genetically heterogeneous group. Twenty percent belong to the newly recognized Xp11.2 translocation-associated family and rare tumors arise from nephroblastoma. Aberrant Wnt signaling through b-catenin mutation has been implicated in nephroblastoma pathogenesis and has been found to synergize with WT1 mutations. To characterize Wnt signaling activity in renal cell carcinomas in young patients, we gathered 34 tumors (three clear cell, ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In other model transmembrane proteins, it has been demonstrated that the minimal distance from the transmembrane domain to a luminal glycosylation site must be between 12 to 15 residues in order for N-linked glycosylation to take place (46). Therefore, it is not surprising that the potential glycosylation site at N53 is not modified since it puts this amino acid within 11 residues from the predicted first transmembrane domain (4,7,52). Similarly, the potential glycosylation site at N945 (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In other model transmembrane proteins, it has been demonstrated that the minimal distance from the transmembrane domain to a luminal glycosylation site must be between 12 to 15 residues in order for N-linked glycosylation to take place (46). Therefore, it is not surprising that the potential glycosylation site at N53 is not modified since it puts this amino acid within 11 residues from the predicted first transmembrane domain (4,7,52). Similarly, the potential glycosylation site at N945 (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Here, the majority of ccRCCs showed strong cytoplasmic or membranous expression. However, no nuclear staining was observed in malignant and normal tissues in this series [6]. …”
Section: Resultsmentioning
confidence: 97%
“…Mice lacking the Apc gene specifically in the kidney are prone to the development of cystic renal cell carcinomas ( Sansom et al, 2005 ). Finally, cytoplasmic accumulation of β-catenin was observed in patients with TFE3 -tRCC, suggesting the presence of a possible link between TFE -factors and WNT-signaling components ( Bruder et al, 2007 ). Together these studies reveal a strong link between hyper-activation of WNT signaling and tumorigenesis in the kidney and reinforce our finding of WNT hyper-activation in TFEB transgenic mice as a critical step of the disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%